Distortion-product Otoacoustic Emissions in Diagnostic Versus Portable Equipment: A Comparison of Animal Models - Novanta, Gabriela Guenther Ribeiro; Pinto, Vanessa Silva; Araújo, Juliana Gusmão de; Serra, Lucieny Martins; Sampaio, Andre Luiz Lopes (International Archives of Otorhinolaryngology, 2025)
Introduction Many protocols carried out in animal studies use equipment developed for humans. Therefore, the equipment available on the market must be known in detail, as well as how the criteria to be evaluated are presented.Objective To analyze the existence of an association between the amplitude and signal-to-noise ratios of distortion-product otoacoustic emissions using two methodologies (diagnostic and portable/screening equipment) in animal models.Methods Experimental study approved by the Animal Use Ethics Committee, with a sample of 28 female Wistar rats, which were subjected to anesthesia, manual otoscopy, and distortion-product otoacoustic emission (DPOAE) examination at 4 to 8 kHz with the 2 pieces of equipment.Results The mean amplitude values with the ILO (Otodynamics Ltd., Hatfield, United Kingdom) and OtoRead equipment (Interacoustics A/S, Middelfart, Denmark) were respectively 20.5 dB and 7.1 dB at 4 kHz; 31.8 dB and 19.37 dB at 6 kHz; and 31.4 dB and 25.1 dB at 8 kHz. The mean signal-to-noise ratios with the ILO and OtoRead equipment were respectively 20.9 dB and 25.1 dB at 4 kHz; 35.8 dB and 37.0 dB at 6 kHz; and 39.7 dB and 40.6 dB at 8 kHz. There was no statistically significant difference in signal-to-noise ratios at 6 and 8 kHz. When the data were classified as normal/abnormal, 100% agreement was found between the methodologies.Conclusion An association was found in the analysis of the mean signal-to-noise ratio at 6 and 8 kHz between the 2 methodologies (diagnosis and portable/screening equipment).
Keywords: otoacoustic emissions; hearing; cochlea; rats